(3GdJMcje cfXGe dJShjI efGRYGJ GdGSJKeGQ GdCLfHj aj Xd GdbGfhfjf GdLRGFQj hGdeUQj (B: s (3eY EdbGA GdVhA Ydj GJaGbjI hGTfWf dSfI (B1965 / s - (3ehfjI LeYjs; (3eMeO HgLJ YHOGddg bGjOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2009)
(3GUHM GdESJKeGQ Gdjhe VQhQI edMI jaQVgG hGbY GdJLGQI GdOhdjI aj Xd GdfXGe GdYGdej GdLOjO hGdEfaJGM GdEbJUGOj(B: (3NGUI HGdfSHI ddOhd GdfGejI(B. (3hbO GOj JOab GdESJKeGQGJ Gdj RjGOI GdefGRYGJ ShGA Jdc GdfGTFI Yf GdELQGAGJ GdGfaQGOjI GdJj JJNPgG GdOhdI Gh Jdc GdfGLeI Yf JZjQ GdXQha GdJj Je GdJYGbO ajgG(B: (3dYd aj GdJMcje GdhSjdI GdeKdj hGdaYGdjI dJShjJgGs
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdJLGQj, (B2009s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMI(B: 283 - 294s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GJaGbjI hGTfWf dSfI (B1965s; (3GSJKeGQ CLfHj s; (3JMcje JLGQj Ohdjs; (3MUGfI GdOhd GdCLfHjIs; (3GJaGbjI Lfja ddJMcje GdOhdjs; (3efXeI GdJLGQI GdYGdejIs; (3caGdI Mbhb GdOaGYs; (3GdTQcGJ eJYOOI GdLfSjGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs